HOW TO STOP PLACING FALSE INFORMATION AND HATE SPEECH ON THE INTERNET? - Knol Radoja, Katarina; Bodul, Dejan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The subject of this paper will be the protection of fundamental human rights from false and offensive information and hate speech on the Internet. The regulations and case law of the national courts of the Republic of Croatia, the ECtHR and EU Court are analyzed. In conclusion, it is stated that the protection of human rights in the digital environment has not yet achieved its precise legal framework, neither at the national nor at the international level. Neither the case law has so far shown clear and unambiguous precision in the interpretation of existing regulations. The right balance between freedom of expression of the media and the right of individuals to protection of personality rights is extremely difficult and challenging to achieve. The media should react in a timely manner to inappropriate content, but the general obligation to 'filter' comments of online media users is incompatible with freedom of expression. Excessive control of information can easily turn into censorship. However, we believe that it is necessary to clearly regulate the rights and obligations of participants on the Internet, because transparency and predictability of accountability is the only way to establish protection of fundamental rights of individuals and certain vulnerable groups.
Keywords: freedom of expression on the Internet; false information; hate speech